WHAT SHOULD BUSINESS MEN KNOW ABOUT ACCOUNTING? - Douglas, A. W. (The Accounting Review, 1927)
This article focuses on the author's views about knowledge of accounting which is needed by a businessmen. The author says that first, a business executive should be sufficiently familiar with the principles of accounting to enable him to appreciate the mutual relations of the important factors in his particular line. Another and all-important exercise of the accounting attitude of mind is needed by the executive in his analysis of the widely differing business conditions which often exist throughout the country. The most definite information on this score can be bad from the traveling salesman, who is usually the best posted man in such matters in his territory. The problem of the executive is then to concentrate his efforts on the section and localities where the going is good, and where business is to be had. On the other hand, he must cut on expenses in the localities where conditions are poor, scrutinize sales and credits and push collections.